Controllable preparation of CuCo2S4 nanotube arrays for high-performance hybrid supercapacitors - Zhang, Kai; Zeng, Hong-Yan; Li, Hao-Bo; Xu, Sheng; Lv, Shi-Bing; Wang, Ming-Xin (Electrochimica acta, 2022)
•The CuCo2S4 nanotube array on Ni foam was prepared by controlled the sulfurization time.•The crystallinity, morphology and electrochemical performance depend on the sulfurization time.•The optimal CuCo2S4/NF8 exhibited excellent electrochemical performances and good cycling stability.•The assembled CuCo2S4/NF8//AC device showed a high energy density 51.8 Wh kg1 at a 700 W kg1. The CuCo2S4 sulfides were fabricated on Ni foam (NF) through a single-step hydrothermal deposition followed by sulfurization at different times. The results from various spectroscopic and microscopic analyses showed that the 3D hollow nanotube CuCo2S4 arrays were formed by the sulfurization, resulting in a larger contact area with the electrolyte and more active sites with high Faraday efficiency. Benefited from the unique nanotube arrays structure and high crystallinity, the optimized CuCo2S4/NF8 electrode material sulfurized for 8 h displayed superior electrochemical performances with the high specific charge of 458.8 C g − 1 at 1.0 A g − 1 as well as good cycling stability with 96.0% retention at 5.0 A g − 1 after 1 000 cycles. Furthermore, a hybrid supercapacitor device based on the CuCo2S4/NF8 as positive electrode and activated carbon as negative electrode was able to deliver an ultrahigh energy density 51.8 Wh kg−1 at a power density 700.0 W kg−1 with 80.0% capacitance retention at 5.0 A g − 1 after 10 000 cycles. This work provided new insights into the sulfurization process and an effective way to optimize the structure of the transition metal sulfides for supercapacitors. [Display omitted]